Students’ Perception on Interprofessional Education - Salmah Orbayinah; Laksmi Putri Utami (Intelektual Pustaka Media Utama, 2015)
Unawareness of the roles and competencies of other health professions has led to many medical and medication errors in the treatment of patients in the hospital. It is considered important to give Interprofessional Education (IPE) to students at pre-clinic and clinical stage in order to have a good understanding about roles of other health professionas. IPE is an interprofessional collaborative learning to support promotive, preventive, curative, rehabilitative and other approches related to health aspect. Perception is among the most important and highly needed skill in the implementation of IPE. This research aimed to determine the effect of IPE learning toward the perception among the students in Faculty of Medicine and Health Science of Universitas Muhammadiyah Yogyakarta (FMHS UMY). This is an observational study adopting a cross sectional design. The sample of students was collected through purposive sampling technique. A number of 94 students met the inclusion criteria, comprised of 21 students of Medical Profession Education, 25 of Dentistry Profession Education, 25 of Nursing Profession Education and 21 Undergraduate students of Pharmacy. Samples were given questionnaire of Interdiciplinary Education Perception Scale. Comparative test was done by Kruskall-Wallis test. From 94 students of FMHS, 75.5% had good perception toward IPE. No significant differences appeared in perception (p=0.285) among the students of FMHS UMY. The Interprofessional Education (IPE) had significant effects toward the perception among the students of FMHS UMY.